Isolasi Senyawa Flavonoid dari Fraksi Amil Alkohol Daun Mangga Golek (Mangifera indica L. cv. Golek) - Maulina Dwi Haryani; Enny Fachriyah; Dewi Kusrini (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Mango plant (Mangifera indica L.) is a tropical fruit plant with high nutrition in the Anacardiaceae family. One of the several varieties of mango plants spread throughout Indonesia, namely mango golek. This study aims to obtain flavonoid isolates and find out the types of flavonoids in the leaves of mango golek. In this study, maceration was carried out to obtain ethanol extract, then followed by phytochemical tests, removal of chlorophyll using distilled water (1: 1), hydrolysis using 2N HCl, followed by liquid-liquid extraction using ethyl acetate and amyl alcohol. In the amyl alcohol fraction, flavonoid was separated using gravity column chromatography with a mixture of eluent n-butanol:n-hexane:methanol (4:2:1). Phytochemical tests showed positive results for alkaloids, saponins, tannins, quinones and flavonoids. UV-Vis spectrophotometer analysis provides absorption at a wavelength of 263 nm while FTIR analysis showed the presence of O-H, C=O, C-O-C aliphatic, and C-O alcohol groups. LC-MS/MS instrument analysis showed m/z of 300 which is the molecular mass of isoflavone compound.